2012
DOI: 10.1159/000334375
|View full text |Cite
|
Sign up to set email alerts
|

Do Additional Cores from MRI Cancer-Suspicious Lesions to Systematic 12-Core Transrectal Prostate Biopsy Give Better Cancer Detection?

Abstract: Background: The comparison of systematic prostate biopsies (PBx) with PBx including additional cores based on magnetic resonance imaging (MRI) of lesions suspicious for prostate cancer (PCa) has been controversial. This study focuses on additional cores based on MRI findings for better cancer detection. Methods: Data were collected from 491 men who underwent transrectal ultrasound-guided PBx: a 12-core PBx (group 1: 395 cases) and a 12-core PBx plus 1–3 additional cores based on MRI (group 2: 96 cases). Compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 61 publications
0
2
1
Order By: Relevance
“…Targeted biopsy identified by MRI may be useful to improve the positive rate on first biopsy. This finding differs from the results of Shigemura et al who reported that only 1.04% of cancers had positive cores in MRI targeted biopsy alone ( 27 ). This difference may be caused by differences in prostate volume (mean 44.82 vs. 31.9 ml) and serum PSA level (mean 9.73 vs. 8.58 ng/ml) between the two studies.…”
Section: Discussioncontrasting
confidence: 99%
“…Targeted biopsy identified by MRI may be useful to improve the positive rate on first biopsy. This finding differs from the results of Shigemura et al who reported that only 1.04% of cancers had positive cores in MRI targeted biopsy alone ( 27 ). This difference may be caused by differences in prostate volume (mean 44.82 vs. 31.9 ml) and serum PSA level (mean 9.73 vs. 8.58 ng/ml) between the two studies.…”
Section: Discussioncontrasting
confidence: 99%
“…Shigemura et al [11] suggested that a 12-core SB can be considered an excellent tool for PCa detection and there may be no need for additional cores based on MRI findings. These data are in contrast to our findings, demonstrating an incremental value of 16% using mpMRI for PCa diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, targeting accuracy relies heavily on challenging cross-modality image-to-image registration [6] and deformable registration methods [7, 8]. MRI-TRUS fusion is most likely superior to traditional systematic methods, but requires further validation and it remains to be tested if it is sufficiently accurate to make a clinical difference [9]. …”
Section: Introductionmentioning
confidence: 99%